Cryopreservation de of shoots and seeds of cedar (Cedrela odorata L.) - García Rojas, Tatiana (2013)
In order to protect the forest resources of Cedrela odorata L., currently threatened, it was considered necessary to establish a protocol for its cryopreservation. Research was conducted using shoots and seeds. Vitrification techniques were evaluated with shoots, using various solutions and rapid freezing in liquid nitrogen (LN). Initially the best results were obtained using incubation for 5 min in PVS3 solution before freezing, survival being 61% after 3 weeks of culture on Murashige and Skoog (MS) medium with 1.0 mg.l-1 BAP and 0.1 mg.l-1 GA3. Moreover, by incubating the apices in 0.3 M sucrose solution for 5 min prior to freezing, the survival rate reached 86% after 2 weeks of culture on MS medium with 1.0 mg.l-1 BAP, 0.1 mg.l-1 GA3 and 0.01 mg.l-1 IAA. When incubation in the solution of 0.3 M sucrose was used and recovery MS medium with 1 mg.l-1 KIN, 0.5 mg.l-1 GA3 and 100 mg.l-1 activated charcoal, the appearance of the surviving shoots improved significantly. For cryopreservation of cedar seeds, the methodology of dehydration and rapid freezing in liquid nitrogen (LN) was evaluated. Seeds with moisture content between 7.9% and 5.5% were placed in 5 ml polypropylene vials and these were directly immersed in NL. The effect of the storage period in NL (1 h, 24 h, 7 days, 1 month, 3 months and 6 months) on seed germination was evaluated. There were no statistical differences in ability of seeds to germinate after storage during different periods.